Developing a Model for Occupational Safety and Health Rrisk Assessment During the Construction Phase of a Metro Tunnel Using Internet of Things (IoT) Technology - Mojtaba Zokaei; Milad Abbasi; Mohsen Vahidnia; Mohamad Zarie; Fardin Zndsalimi; Mohsen Falahati (بهداشت و ایمنی کار)
Introduction: Nowadays, the statistics prove that the underground construction projects in the country are increasing, as well as the number of accidents arising from the unsafe condition of these projects. The purpose of this study was to create a framework of safety and health risk management in the construction phase of the Tehran Metro Line 7 tunnel, using IoT technology. Material and Methods: In the first stage, the national safety and health standards, laws and requirements related to the mentioned hazards were collected. In the second stage, the criteria and permissible limits of exposure to occupational hazards were determined. Next, sensors with optical, auditory, gas detection, and visual capabilities connected to the network were examined, and computer programming and comparing sensor information with the specified standards were carried out. Finally, intelligent warning and control systems related to the determined hazards were proposed. Results: In this study, a combined model of risk management utilizing IoT for controlling and monitoring safety and health hazards such as sound, light, explosive and toxic gases was proposed. According to the model, sensors for detecting the mentioned hazards were determined and coded based on the permissible limit of each of the harmful factors. Conclusion: This study has shown that by employing specialized IT and safety knowledge and utilizing relevant software and hardware, the concept of the Internet of Things can be utilized in precise monitoring of the concentration levels of flammable and toxic gases, as well as monitoring of physical agents such as noise and light in various workplace, such as metro tunnel construction sites.